Thromboelastometric Profiles of Horses Affected by Exercise-Induced Pulmonary Hemorrhages - Alessia Giordano; Cecilia Meazza; Marco Salvadori; Saverio Paltrinieri (Veterinary Medicine International)
Exercise-induced pulmonary hemorrhage (EIPH) commonly occurs in race horses. Thromboelastometry (TEM) investigates the whole hemostatic process by evaluating the viscoelastic properties of the blood clot from its formation to fibrinolysis. The aim of this study was to assess whether horses with EIPH have abnormal thromboelastometric profiles. Intrinsic and extrinsic pathways, fibrinogen activity and fibrinolysis were investigated by TEM before and after the race in negative controls and in horses on which EIPH was confirmed by bronchoscopy. Compared with controls, horses with EIPH had an increased coagulability in both pre- and postrace samplings, especially for the intrinsic pathway and for the fibinrolytic activity. These results suggest that coagulation is preactivated in horses prone to develop EIPH, possibly due to recent or recurrent hemorrhage.